2000
DOI: 10.1002/chin.200001149
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Anticonvulsant Activity of New 4‐Aminopyrazoles and 5‐Aminopyrazol‐3‐ones.

Abstract: Synthesis and Anticonvulsant Activity of New 4-Aminopyrazoles and 5-Aminopyrazol-3-ones.-The title pyrazole derivatives (I)-(III), prepared by literature methods, are tested for their anticonvulsant activity. While 4-aminopyrazole derivative (Ia) as well as its p-chlorophenyl analogue possess sodium channel blocking activity, all 5-aminopyrazole derivatives (II) and (III) are inactive due to incorrect distance between endocyclic and exocyclic NH groups. -(LANKAU, H.-J.; MENZER, M.; ROSTOCK, A.; ARNOLD, TH.; RU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Compound 12 (Figure 6) is characterised by a methyl group at position 3 and by a substituted phenyl ring at position 5; research evidenced some anticonvulsant activity, and the authors demonstrated the importance of the distance between the exocyclic NH 2 group and the endocyclic NH for this type of pharmacological activity [44]. More recently, interesting results have been obtained for similar 4AP analogues tested as anticonvulsant agents [45].…”
Section: -Aminopyrazoles (4aps)mentioning
confidence: 96%
“…Compound 12 (Figure 6) is characterised by a methyl group at position 3 and by a substituted phenyl ring at position 5; research evidenced some anticonvulsant activity, and the authors demonstrated the importance of the distance between the exocyclic NH 2 group and the endocyclic NH for this type of pharmacological activity [44]. More recently, interesting results have been obtained for similar 4AP analogues tested as anticonvulsant agents [45].…”
Section: -Aminopyrazoles (4aps)mentioning
confidence: 96%